The Use Of Torture In The War On Terror: Should This 'Exceptional Measure' Be Justified In 'Exceptional Times'? - Durosaro, Wuraola Olufunke (American Journal of Humanities and Social Sciences, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--> This work critiques the arguments for and against the use of torture in combating terrorism from a human rights perspective. It examines whether or not there should be an absolute ban on the use of torture by states on terrorism suspects and whether torture be reserved as an extreme measure in exceptional circumstances keeping in mind the following human rights: the right to legal recourse when human rights have been violated, even if the violator was acting in an official capacity, the right to life, the right to liberty and freedom of movement, the right to equality before the law, the right to presumption of innocence till proven guilty, the right to appeal a conviction, etc. The works concludes therefore that even though the state has the right to do all within its powers to protect its citizens and territory by adopting any means within its reach to combat terrorism the anti-human right approach of the use of torture may not be the best solution. It is recommended that there should be an absolute prohibition of the use of torture in the war on terror and the work proposes the search of another means which will not mock the dignity of the human person and lay a bad precedent for future government. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->